Bone biopsy protocol for advanced prostate cancer in the era of precision medicine. Issue 5 (19th December 2017) - Sailer, Verena; Schiffman, Marc H.; Kossai, Myriam; Cyrta, Joanna; Beg, Shaham; Sullivan, Brian; Pua, Bradley B.; Lee, Kyungmouk Steve; Talenfeld, Adam D.; Nanus, David M.; Tagawa, Scott T.; Robinson, Brian D.; et al.
Abstract : BACKGROUND: Metastatic biopsies are increasingly being performed in patients with advanced prostate cancer to search for actionable targets and/or to identify emerging resistance mechanisms. Due to a predominance of bone metastases and their sclerotic nature, obtaining sufficient tissue for clinical and genomic studies is challenging. METHODS: Patients with prostate cancer bone metastases were enrolled between February 2013 and March 2017 on an institutional review board‐approved protocol for prospective image‐guided bone biopsy. Bone biopsies and blood clots were collected fresh. Compact bone was subjected to formalin with a decalcifying agent for diagnosis; bone marrow and blood clots were frozen in optimum cutting temperature formulation for next‐generation sequencing. Frozen slides were cut from optimum cutting temperature cryomolds and evaluated for tumor histology and purity. Tissue was macrodissected for DNA and RNA extraction, and whole‐exome sequencing and RNA sequencing were performed. RESULTS: Seventy bone biopsies from 64 patients were performed. Diagnostic material confirming prostate cancer was successful in 60 of 70 cases (85.7%). The median DNA/RNA yield was 25.5 ng/μL and 16.2 ng/μL, respectively. Whole‐exome sequencing was performed successfully in 49 of 60 cases (81.7%), with additional RNA sequencing performed in 20 of 60 cases (33.3%). Recurrent alterations were as expected, including those involving the AR, PTEN, TP53, BRCA2, and SPOP genes. CONCLUSIONS: This prostate cancer bone biopsy protocol ensures a valuable source for high‐quality DNA and RNA for tumor sequencing and may be used to detect actionable alterations and resistance mechanisms in patients with bone metastases. Cancer 2018;124:1008‐15. © 2017 American Cancer Society . Abstract : Biopsies from patients with prostate cancer bone metastases can provide high‐quality tissue for next‐generation sequencing. The authors believe the protocol described in the current study is widely applicable to all bone metastases.